Implementation of Women's Empowerment and Child Protection Policies in the Women-Friendly and Child-Caring Village Program - Dermawan, Wahyu Rahmat; Sandra, Gustika (Moccasin Journal De Public Perspective, 2024)
This study examines the implementation of the Women-Friendly and Child-Caring Village Program (DRPPA) in Rembangkepuh Village, Ngadiluwih District, East Java Province, focusing on women’s empowerment and child protection. Using a qualitative descriptive approach, the research explores the factors influencing the success of the DRPPA program, including policy clarity, human resources, budget adequacy, and community participation. Data were collected through in-depth interviews with village officials, SAPA volunteers, and community leaders, as well as document analysis of program reports. The findings show that the DRPPA program has had a positive impact on reducing child marriages, increasing women’s economic participation, and improving child protection mechanisms. However, challenges such as limited budgets and cultural barriers remain significant. The study highlights the need for increased community engagement and financial resources to ensure the sustainability and effectiveness of the program.